1988
DOI: 10.1002/lsm.1900080507
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser ablation of venous thrombus: Implications for a new approach in the treatment of pulmonary embolus

Abstract: Laser radiation was employed to ablate venous thrombus or emboli with parameters that would not injure endovascular tissues. Output from a 482-nm, 1-microsec pulsed dye laser was delivered through a 320-microns-diameter fiber to in vitro samples of fresh thrombus (T), venous or pulmonary emboli (VE), inferior vena cava (IVC), pulmonary artery (PA), pulmonary valve, and endocardium (atrial and ventricular). The mean threshold fluences for ablation of T and VE were 1.1 and 5.1 J/cm2, respectively. In contrast, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…There are two major findings in this study: (1) Solidstate, pulsed-wave, mid-infrared laser irradiation can induce fibrinolysis by mechanical disruption of the lased clot, in contrast to selective thrombolysis, which is achieved by other wavelength lasers, such as the pulsed dye-laser [11]; (2) thin fibrin fibers are more resistant than thick fibers to the photoacoustic effect of this wavelength energy.…”
Section: Discussionmentioning
confidence: 99%
“…There are two major findings in this study: (1) Solidstate, pulsed-wave, mid-infrared laser irradiation can induce fibrinolysis by mechanical disruption of the lased clot, in contrast to selective thrombolysis, which is achieved by other wavelength lasers, such as the pulsed dye-laser [11]; (2) thin fibrin fibers are more resistant than thick fibers to the photoacoustic effect of this wavelength energy.…”
Section: Discussionmentioning
confidence: 99%
“…The linear absorption coefficients of Nd:YAG laser light for oxyhaemoglobin, deoxyhaemoglobin and melanin are 5 cm -1, 0.5 cm -1 and 20 cm -1, respectively [1,[16][17][18]. Since the amount of thermal energy generated by an absorbing structure is a function of the quanta of light initially absorbed, one would expect melanin granules to radiate more heat than blood (even though other important factors have to be taken into account).…”
Section: (A) Absorption By Blood and Melanin And Other Optical Considmentioning
confidence: 99%
“…Clinical trials have demonstrated the efficacy of laser thrombolysis for coronary vessels [6,8,10,11]. An excellent review of lasers in cardiology was written by Topaz [10] and includes sections on the use of lasers for treatment of acute myocardial infarction and for peripheral laser angioplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Laser thrombolysis, the clearing of thrombus-obstructed arteries by means of laser energy, has been investigated extensively and demonstrated in clinical situations [1][2][3][4][5][6][7][8][9][10][11]. Clinical trials have demonstrated the efficacy of laser thrombolysis for coronary vessels [6,8,10,11].…”
Section: Introductionmentioning
confidence: 99%